Prediction of Heart Disease Using Regression Tree - M. Lutimath, Nagaraj; B N, Arathi; M, Shona (International Journal of Engineering and Technology, 2018)
Decision trees are an important paradigm in machine learning. They are simple and very effective classification approach. The decision tree identifies the most important features of a given problem. The heart disease has a set of distinct values affecting the heart. It includes blood vessel disorders such as irregular heart beat issues, weak heart muscles, congenital heart defects, cardio vascular disease and coronary artery disease. Coronary heart disorder is a familiar type of heart disease. It reduces the blood flow to the heart leading to a heart attack. In this paper the available data set of the patients suffering from heart disease is analyzed. R language is used to predict the accuracy.Â